Cancer-specific glycosylation of CD13 impacts its detection and activity in preclinical cancer tissues - Barnieh, Francis M.; Galuska, Sebastian P.; Loadman, Paul M.; Ward, Simon; Falconer, Robert A.; El-Khamisy, Sherif F. (iScience, 2023)
Harnessing the differences between cancer and non-cancer tissues presents new opportunities for selective targeting by anti-cancer drugs. CD13, a heavily glycosylated protein, is one example with significant unmet clinical potential in cancer drug discovery. Despite its high expression and activity in cancers, CD13 is also expressed in many normal tissues. Here, we report differential tissue glycosylation of CD13 across tissues and demonstrate for the first time that the nature and pattern of glycosylation of CD13 in preclinical cancer tissues are distinct compared to normal tissues. We identify cancer-specific O-glycosylation of CD13, which selectively blocks its detection in cancer models but not in normal tissues. In addition, the metabolism activity of cancer-expressed CD13 was observed to be critically dependent on its unique glycosylation. Thus, our data demonstrate the existence of discrete cancer-specific CD13 glycoforms and propose cancer-specific CD13 glycoforms as a clinically useful target for effective cancer-targeted therapy. [Display omitted] •Removal of CD13 glycans selectively impacts its detection and activity in cancer•Data indicate the existence of discrete cancer-specific CD13 glycoforms•Targeting cancer-specific proteins is an effective and safer anti-cancer approach•Cancer-specific CD13 glycoform is a promising target for cancer-targeted therapy Glycobiology; Molecular biology; Cancer